Mediasi Penal Tindak Pidana Kecelakaan Lalu Lintas Yang Menyebabkan Korban Jiwa Berdasarkan Keadilan Restoratif - Syauqi Mahendra; Nahdhah Nahdhah; Adwin Tista (Scholar Center, 2021)
Penal mediation is a means of seeking justice capable of providing a thorough and satisfactory settlement by both parties outside the court. In the case of a traffic accident that causes a fatality, penal mediation is conducted based on restorative justice. The purpose of this study is to find out the position of mediation of traffic accidents that cause fatalities in the Indonesian criminal justice system and to know the concept in the mediation of traffic accidents that cause fatalities based on restorative justice. The method uses in this study is pure legal research. Pure legal research is applied by using literature studies. The results are: First, the position of penal mediation in fatality traffic accidents has no umbrella act. Second, the concept of penal mediation in the traffic accidents that cause fatalities in Article 15 (2) k, Article 16 (1) L and (2), Article 18 (1) and (2) of Act 2/2002 (Police Act) and The National Chief of Police Letter Number Pol: B/322/XII/2009/SDEOPS dated 14/12/2009 is the legal basis for the police in taking discretionary action. But the letter Pol: B/322/XII/2009/SDEOPS also mentioned that penal mediation is only applicable for small losses. It means that in the case of traffic accidents that cause fatalities, the law is not accommodating out-of-court settlements.